Serum Concentration and Chemotactic Activity of E-selectin (CD62E) in Inflammatory Bowel Disease - B. Vainerc; O. H. Nielsen (Mediators of Inflammation)
E-selectin (CD62E) is an endothelial specific glycoprotein belonging to the selectin family of adhesion molecules. Because a high expression of this molecule at intestinal mucosal surfaces in inflammatory bowel disease (IBD) has been described earlier, the aim was to assess serum levels of E-selectin (sE-selectin) and to correlate it to disease activity, and further to evaluate its chemotactic properties at physiological concentrations. Levels of sEselectin were measured by a sandwich ELISA technique in 31 IBD patients together with 15 healthy volunteers. In ulcerative colitis the median value was 0.46 nM (0.16–0.75), in Crohn’s disease 0.47 nM (0.22–1.24), and in healthy controls 0.34 nM (0.22–0.83). No statistically significant differences in sE-selectin were revealed between these groups (p>0.05). The in vitro chemotactic capabilities of E-selectin (in the concentration range of 0.10–31.4 nM) were assessed using the leading front technique. A significantly increased migratory response was found at concentrations of 1.00 (p<0.05) and 3.14 nM (p<0.02). It is concluded that sE-selectin in contrast to sICAM-1 does not act as a sensitive indicator of local immune activation in IBD. However, E-selectin may be important for recruitment and accumulation of neutrophilic granulocytes and other phagocytes involved in the inflammatory process seen in IBD. Future investigations are encouraged in order to reveal its in vivo effects.